Analysis of results of the study concerning readiness formation of stomatological faculty students to professional activity by means of interactive techniques - I. V. Lukashevych; V. P. Prysyazhnyuk; I. V. Prysiazhniuk; C. P. Koshelanyk (Kazimierz Wielki University, 2019)
The introduction of innovative approaches to training of dental specialists requires reasonable analysis of results of the study concerning readiness of future dental practitioners for professional activity by means of interactive technologies, which is the subject of our research. The article presents the results establishing the levels of formation of dental faculty students' readiness for their future professional activity at the stages of entrance and final testing.